Association Between Self-Esteem and Cyber Victimization: The Mediating Roles of Digital Game Playing and Cyberbullying - Eryilmaz, Ali; Huebner, E. Scott; Yildirim-Kurtulus, Hacer; Kara, Ahmet (ROUTLEDGE JOURNALS, TAYLOR & FRANCIS LTD, 2025)
BackgroundToday, the intensive use of technology necessitates more research on cyberbullying and victimization among adolescents.PurposeThe purpose of this study was to evaluate a proposed model of the associations between self-esteem, digital game playing, cyberbullying, and victimization in early adolescents.MethodsA total of 312 early adolescents participated based on the criterion sampling method. The age range of the adolescents was 10-14 years (Mean = 12.63; SD = 0.60). Two-stage structural equation modeling was used to analyze the data. Bootstrapping analysis was used to test mediation effects.ResultsThe findings revealed the serial mediating relations of digital game playing and cyberbullying in the association between early adolescents' self-esteem and cyber victimization.DiscussionThe results emphasize the role of individual differences in adolescents' self-esteem as a significant factor in cyber victimization. This relationship operates through the behavioral pathways of digital game use and cyberbullying.Translation to Health Education PracticeBased on the research findings, health educators can encourage students in this developmental period to establish healthier relationships in the digital world and develop strategies to protect mental health. In this direction, health educators should aim to develop healthy digital gaming habits in students by considering the negative effects of digital game addiction on cyber victimization. For this purpose, educators can organize awareness-raising educational programs against digital game addiction and guide students in determining balanced play times
Keywords: INTERNET ADDICTION; MIDDLE SCHOOL; MENTAL-HEALTH; LIFE-STYLE; ADOLESCENTS; DEPRESSION; ONLINE; AGGRESSION; BEHAVIORS; ANXIETY; Public, Environmental & Occupational Health